المجموعة القصصية (أخاديد على شريط الزمن) لبشير خلف: دراسة فنية - اسمهان حفصي (My University, 2023)
Summary : The short story is considered a form of fictional literature, and its artistic formation is nothing but a reflection of one of the psychological states of the author in terms of reading, as these psychological functions of interest, doubt, memory, imagination, patience, and all that occur in each short story appear very clearly. In particular, the writer Bashir Khalaf made this collection of stories, especially during reading and analysis, in some stories such as the story of a peddler and the story of a meeting in a clinic. These titles carry a lot of meanings, and he also employed many techniques, the most important of which is anticipation and retrieval of the sequence of events in a good way. He also employed places and gave each place a different meaning, as there was little dialogue in this group due to the lack of personalities. ------------------------ الملخص تعتبر القصة القصيرة شكل من أشكال الأدب القصصي و إن التشكيل الفني لها ما هو إلا انعكاس لإحداى الحالات النفسية للمؤلف من ناحية القراءة حيث تظهر بوضوح شديد هذه الوظائف النفسية المتمثلة في الاهتمام و الشك و الذاكرة و الخيال و الصبر و كل تحدث فعلها في كل قصة قصيرة بشكل خاص كما جعل الكاتب بشير خلف في هذه المجموعة القصصية و خاصة أثناء القراءة و التحليل في بعض القصص مثل قصة بائع متجول و قصة لقاء في عيادة فهذه العناوين تحمل في طياته الكثير من المعني كما وظف العديد من التقنيات أهمها الاستباق و الاسترجاع لتسلسل الأحداث بصفة جيدة و أيضا وظف الأمكنة و جعل لكل مكان دلالة مختلفة كما كان الحوار قليلا في هذه المجموعة بسبب قلة الشخصيات. --------------------- Résumé: La nouvelle est considérée comme une forme de littérature de fiction, et sa formation artistique n'est que le reflet d'un des états psychologiques de l'auteur en matière de lecture, car ces fonctions psychologiques d'intérêt, de doute, de mémoire, d'imagination, de patience, et de toutes qui se produisent dans chaque nouvelle apparaissent très clairement. En particulier, l'écrivain Bashir Khalaf a fait ce recueil d'histoires, notamment en lisant et en analysant certaines histoires, comme l'histoire d'un colporteur et l'histoire d'une réunion dans une clinique, car ces les titres ont beaucoup de sens, il emploie aussi des lieux et donne à chaque lieu un sens différent, car il y a peu de dialogue dans ce groupe faute de personnalités.